Hypertriglyceridemia: A simple approach to identify insulin resistance and enhanced cardio-metabolic risk in patients with prediabetes. (October 2016) - Abbasi, Fahim; Kohli, Payal; Reaven, Gerald M.; Knowles, Joshua W.
Highlights: Risk of cardiovascular disease and diabetes is not uniform in prediabetes. Fasting triglycerides ⩾1.7 mmol/L identified a high-risk subset of prediabetes. The subset was more insulin resistant with an adverse cardio-metabolic risk. This simple approach can be used for risk stratification of persons with prediabetes. Abstract: Aims: Prediabetes (PreDM) is a metabolically heterogeneous condition, differing in degree of insulin resistance and risk of type 2 diabetes mellitus and coronary heart disease (CHD). This study was initiated to evaluate the hypothesis that a fasting plasma triglyceride (TG) concentration ⩾1.7 mmol/L can aid in identifying the subset of individuals with PreDM who are most insulin resistant and at greatest risk to develop CHD as well as type 2 diabetes mellitus. Methods: In this cross-sectional study, measurements were made of: (1) steady-state plasma glucose (SSPG) concentration during the insulin suppression test to ascertain degree of insulin resistance and (2) conventional CHD risk factors in 587 apparently healthy individuals with normal fasting plasma glucose (NFG, n  = 370) or PreDM ( n  = 217). Results: Subjects with PreDM were significantly ( P  < 0.001) more insulin resistant (higher SSPG concentrations) and had a more adverse CHD risk profile than those with NFG. A TG concentration ⩾1.7 mmol/L identified a subset of individuals with PreDM (38%) who had a higher mean SSPG concentration (11.3 ± 3.5 mmol/L vs. 9.3 ± 3.9 mmol/L, P  < 0.001), were more likely to be insulin resistant (66% vs. 39%, P  < 0.001), and had a more adverse CHD risk factor profile. Conclusions: Measurement of fasting TG concentration in individuals with PreDM may provide a simple clinical approach to identify those who are insulin resistant, at enhanced risk of CHD, and more likely to develop type 2 diabetes mellitus.